2020
DOI: 10.1002/prp2.567
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic and exposure‐response analysis of eptinezumab in the treatment of episodic and chronic migraine

Abstract: Eptinezumab is a humanized mAb that targets calcitonin gene‐related peptide and is under regulatory review for the prevention of episodic and chronic migraine (EM, CM). It is important to determine whether exposures achieved with intravenous (IV) administration of eptinezumab achieve desired pharmacologic effects. Population pharmacokinetics, including dose‐ and exposure‐response analyses, were performed using patient‐level data from the eptinezumab clinical trial program with IV doses ranging from 10 to 1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 29 publications
0
55
0
Order By: Relevance
“…Early onset and sustained response during the PROMISE-2 study may be a result of the pharmacokinetic properties of eptinezumab and its route of administration. Maximum plasma concentrations are achieved immediately upon completion of delivery of the IV administration and persist throughout the dosing interval with a terminal elimination half-life of 27 days [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early onset and sustained response during the PROMISE-2 study may be a result of the pharmacokinetic properties of eptinezumab and its route of administration. Maximum plasma concentrations are achieved immediately upon completion of delivery of the IV administration and persist throughout the dosing interval with a terminal elimination half-life of 27 days [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 Eptinezumab is delivered by a 30-minute IV administration with rapid attainment of maximum plasma concentration by the end of IV administration. 14…”
Section: Discussionmentioning
confidence: 99%
“…By intravenous (IV) administration over 30 minutes, eptinezumab has 100% bioavailability and achieves maximum plasma concentration at the end of IV administration. 14 Pharmacokinetic results coupled with data from phase 2 studies 15,16 suggested that migraine preventive efficacy of eptinezumab may begin immediately, leading to the inclusion of the percentage of patients reporting a migraine headache on day 1 as a prespecified and alpha-controlled endpoint in pivotal phase 3 trials conducted in patients with episodic (PROMISE-1) and chronic (PROMISE-2) migraine. In both pivotal trials, the percentage of patients reporting a migraine on day 1 was reduced by more than 50% compared to baseline in eptinezumab-treated patients and by approximately 25% in placebo patients.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-CGRP monoclonal antibodies are less hepatotoxic than gepants, their metabolism is based on reticuloendothelial uptake. Since monoclonal antibodies are not known to be eliminated via renal pathways or metabolized in the liver, renal and hepatic impairment are not expected to impact their pharmacokinetics [111][112][113][114][115][116][117][118].…”
Section: Anti-cgrp Monoclonal Antibodies (Mabs)mentioning
confidence: 99%
“…Steady-state plasma concentrations are achieved with the first dose of the once every three months dosing schedule. Eptinezumab's distribution volume is approximately 3.7 L, and biological half-life is about 27 days [117].…”
Section: Eptinezumabmentioning
confidence: 99%